Návrh komunikační strategie pro Ski areál Šacberk - Krejčová, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Cílem práce je návrh komunikačního mixu pro Ski areál Šacberk tak, aby byla komunikace se zákazníky efektivnější a formy propagace zviditelnily všechny přednosti areálu. Analyzuje současný stav tohoto mixu a zabývá se návrhy možného zlepšení a rozšíření reklamní kampaně do dalších oblastí České republiky tak, aby areál získal nové zákazníky a zároveň udržoval ty současné.

The aim of this thesis is to propose the communication mix for Šacberk Ski Resort. The objective of this thesis is the improvement of communication with customers and promotion of the company. Advertising campaign should make all the advantages of the company more visible. Diploma thesis evaluates current situation of the mix and proposes improvements and expansion of the advertising campaign to other regions of the Czech Republic. The new communication mix should lead to improving the current situation, gaining new customers and keeping current customers.
Communication Strategy Proposal for the Ski Resort Šacberk
Keywords: Marketingový mix; komunikační mix; Ski areál Šacberk.; Marketing mix; communication mix; Ski resort Šacberk.